2022
DOI: 10.1007/s11258-022-01222-z
|View full text |Cite
|
Sign up to set email alerts
|

Foliar water uptake in the needles of Pinus torreyana

Abstract: The natural habitat of Pinus torreyana, the Torrey pine, is restricted to two locales in coastal Southern California that experience substantial fog and low clouds during the dry months of a Mediterranean climate. In similar semi-arid climate systems that encounter fog or low clouds, many plants can capture atmospheric moisture and are capable of direct foliar water uptake to reduce water stress. In this study, we investigated if the needles of P. torreyana are also capable of direct water uptake. In addition … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
(64 reference statements)
1
5
0
Order By: Relevance
“…Furthermore, the vertical accumulation of Mg from the Florin ring aperture to the chamber appears to indicate the stomatal seawater uptake, lowering the possibility of random particle deposition (Figure 6). A recent report of stomatal water uptake on Pinus species also supports a similar phenomenon occurring on P. thunbergii needles (Tianshi & Chau, 2022). Stomatal penetration by seawater and solutes in asymptomatic leaves could be regarded as the initial phase of seawater salt‐induced injury in pine species growing in coastal areas.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Furthermore, the vertical accumulation of Mg from the Florin ring aperture to the chamber appears to indicate the stomatal seawater uptake, lowering the possibility of random particle deposition (Figure 6). A recent report of stomatal water uptake on Pinus species also supports a similar phenomenon occurring on P. thunbergii needles (Tianshi & Chau, 2022). Stomatal penetration by seawater and solutes in asymptomatic leaves could be regarded as the initial phase of seawater salt‐induced injury in pine species growing in coastal areas.…”
Section: Discussionsupporting
confidence: 70%
“…In the present study, it was shown that, as the seawater salt crystals containing NaCl and Mg were finally deposited in the stomatal chambers after the evaporation of seawater drops, FWU had occurred through the stomata. The seawater drops on pine needles are much larger in diameter and cover several stomatal complexes, as exemplified in Pinus torreyana (Tianshi & Chau, 2022). The establishment of FWU would entail the formation of a continuous liquid water film (assumed to be 100 nm or less in thickness) connecting the leaf surface with the apoplastic liquid water (Burkhardt, 2010; Burkhardt et al., 2012; Schreel & Steppe, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the foliar water uptake pathway between angiosperms and conifers may have their roots in the diverging evolutionary ecology of these two clades, in which changes in stomatal function may relate to uptake, photosynthetic rates, and other strategic differences. Stomatal density most likely increases surface hydraulic resistance in conifers because conifers possess large wax plugs in their stomata and their density is associated with a general abundance of epicuticular wax (Chin, Guzmán‐Delgado, Sillett, Orozco, et al, 2022; Chin, Guzmán‐Delgado, Sillett, Kerhoulas, et al, 2022; Leyton & Juniper, 1963; Tianshi & Chau, 2022). Larger guard cells, which are associated with larger stomatal pores, were the individual trait most associated with foliar water uptake in conifers, a trait previously found to reduce surface hydraulic resistance in Sequoia (Chin, Guzmán‐Delgado, Sillett, Orozco, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The interplay of leaf surface wettability and FWU is not strictly relational. Although higher wettability has often been linked to increased FWU capacity or rate (Cavallaro et al, 2022; Pan et al, 2021; Tianshi & Chau, 2022), and species with hydrophobic leaves are assumed to be less likely to benefit from water deposition from fog and dew, other studies have noted no significant relationship between FWU and leaf surface wettability (Chin et al, 2023b; Matos & Rosado, 2016). This also reflects the diversity of strategies underlying FWU among different plant groups (Chin et al, 2023a; dos Santos Garcia et al, 2022).…”
Section: Discussionmentioning
confidence: 99%